INTERNATIONAL COOPERATION AS A LEVER FOR ENHANCING THE DEVELOPMENT OF THE TOURISM AND HOSPITALITY SECTOR IN UKRAINE - SEMYKINA, Maryna (Herald of Khmelnytskyi National University. Economic sciences, 2024)
This article develops scientific and practical recommendations for shaping effective international cooperation mechanisms within Ukraine's tourism and hospitality sector, specifically addressing the challenges of operating under martial law and the needs of post-war recovery. The recommendations aim to foster innovative renewal, enhance the competitiveness of personnel, and attract foreign partners for the restoration of tourism infrastructure. The study defines the essence of international cooperation and substantiates its role as a pivotal lever for the industry's reconstruction and innovative development. The methodological foundation of this research includes a comparative analysis of global post-conflict tourism recovery case studies and a systemic analysis of the current challenges facing the Ukrainian tourism business. Key challenges identified include the widespread destruction of critical tourism infrastructure, severe personnel shortages due to displacement and mobilization, and a dramatic decline in inbound tourist flows. Based on this comprehensive analysis, the paper proposes a set of targeted recommendations for establishing robust partnership mechanisms. Key priorities include attracting foreign direct investment for infrastructure restoration through the creation of joint investment funds, public-private partnerships, and specialized war risk insurance mechanisms. To address the human capital crisis, the study advocates for joint educational projects and mutual recognition of professional qualifications with EU partners. Furthermore, the article underscores the critical need to implement internationally recognized safety and security standards to rebuild tourist confidence, supported by joint marketing campaigns that promote verified "safe-travel" routes. The research concludes that a systemic, multi-level approach to international cooperation—encompassing institutional, financial, infrastructural, and human resource dimensions—is a strategic driver for the comprehensive transformation and sustainable renewal of the sector. The findings prove that such integrated partnerships are essential for ensuring the long-term resilience and innovative modernization of Ukraine's tourism industry.
Keywords: international cooperation; tourism and hospitality sector; post-war recovery; martial law; innovative development; human capital; tourism infrastructure